2023
DOI: 10.3390/s23218926
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Assessment of Cognitive Workload Using Neural, Subjective and Behavioural Measures in Smart Factory Settings

Zohreh Zakeri,
Arshia Arif,
Ahmet Omurtag
et al.

Abstract: Collaborative robots (cobots) have largely replaced conventional industrial robots in today’s workplaces, particularly in manufacturing setups, due to their improved performance and intelligent design. In the framework of Industry 5.0, humans are working alongside cobots to accomplish the required level of automation. However, human–robot interaction has brought up concerns regarding human factors (HF) and ergonomics. A human worker may experience cognitive stress as a result of cobots’ irresponsive nature in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…While previous works ( Kulić and Croft, 2007 ; Arai et al, 2010 ; Koppenborg et al, 2017 ; Kühnlenz et al, 2018 ; Gervasi et al, 2022 ; Zakeri et al, 2023 ) in HRC investigated a robot’s movement speed and proximity as factors that induce stress and anxiety, these factors have not been shown to induce boredom or flow. Based on our previous exploratory study ( Mondellini et al, 2023 ), we identified production rate as a factor influencing boredom and flow, in addition to anxiety.…”
Section: Methodsmentioning
confidence: 98%
“…While previous works ( Kulić and Croft, 2007 ; Arai et al, 2010 ; Koppenborg et al, 2017 ; Kühnlenz et al, 2018 ; Gervasi et al, 2022 ; Zakeri et al, 2023 ) in HRC investigated a robot’s movement speed and proximity as factors that induce stress and anxiety, these factors have not been shown to induce boredom or flow. Based on our previous exploratory study ( Mondellini et al, 2023 ), we identified production rate as a factor influencing boredom and flow, in addition to anxiety.…”
Section: Methodsmentioning
confidence: 98%
“…At the same time, a distinction should be made between a model and a copy, with a model being a description of something [16,17].…”
Section: Defining the Term "Model" For The Studymentioning
confidence: 99%